Pengembangan Kampung Wisata Jodipan Ditinjau dari Partisipasi Sosial Masyarakatnya - Alya Nafisa Fidelista; Delia Suci Audri; Diana Savitri; Muhammad Hafizh Ramadhan; Novi Sunu Sri Giriwati; Sri Utami Azis; Susilo Kusdiwanggo (Archvisual: Jurnal Arsitektur dan Perencanaan, 2023)
Jodipan Tourism Village (KWJ) is the first colorful tourist village in Malang City. The formation of KWJ stems from the initiative of a group of students working together with PT. Indana and the local community to create a better environment for Jodipan Tourism Village. This village used to be a slum settlement which is now transformed into a colorful village that attracts the attention of local and foreign tourists. Increasing the function of the village as a tourist attraction apart from providing economic and social benefits for local residents, also affects their daily lives. In dealing with these changes, there is the role of social participation of local residents to maintain the sustainability of the tourism function and their own survival. This research uses literature review, interview, and descriptive data analysis methods to explore the social participation of residents in the development of Kampung Warna-Warni Jodipan before revitalization, after revitalization, and now. The results showed that the form of social participation of the citizens was influenced by the conditions and problems faced at that time and was a form of adaptation to the new environment that was formed. With residents carrying out social participation, residents can improve the economy because of tourism activities in Jodipan Colorful Village.